Bilateral breast nodules as an unusual manifestation of 17α-hydroxylase/17,20-lyase deficiency - Zhang, Minchun; Huang, Xing; Li, Qifeng; Gui, Shuyan; Lin, Shiwei; Fan, Gang; Yang, Jing (Frontiers in Endocrinology, 2025)
Introduction17α-hydroxylase/17,20-lyase deficiency (17-OHD) typically presents with sexual infantilism, hypertension, and hypokalemia. However, phenotypic variability, particularly breast development, may obscure diagnosis. This study aims to characterize an atypical presentation of 17-OHD with preserved breast development and breast nodules, and to evaluate clinical and hormonal features associated with breast development through a systematic literature review.MethodsA 38-year-old woman with bilateral breast nodules and ductal ectasia was diagnosed with 17-OHD, confirmed by CYP17A1 variants. A literature review of 17-OHD cases with near-complete breast development (Tanner stage 4–5) was conducted to analyze clinical, hormonal, and genotypic features.ResultsThe patient exhibited classic signs of 17-OHD including hypertension, hypokalemia, adrenal hyperplasia, and hypogonadism, but also presented with atypical bilateral breast nodules and mammary duct ectasia. Hormone therapy resulted in clinical improvement and regression of the breast findings. Literature analysis of 43 patients with breast development showed that patients with 46,XX were diagnosed later than 46,XY (29.5 ± 11.5 vs. 19.8 ± 6.9 years, P = 0.0095). Estradiol was more often subnormal in 46,XX, while both groups showed progesterone excess and androgen deficiency. Pubic hair development differed by karyotype (P = 0.027), which was more advanced in the 46,XY group. Genetic data revealed that breast development was associated with non-null CYP17A1 variants, and most variants clustered in exons 5–8, with exon 8 as a hotspot.ConclusionThis case broadens the phenotypic spectrum of 17-OHD, highlighting that preserved breast development and benign breast lesions may delay diagnosis. Literature review suggests partial loss-of-function variants contribute to this phenotype. Greater awareness is essential to prevent misdiagnosis and unnecessary interventions.